Nickel-Catalyzed Amination of α-Aryl Methyl Ethers - Patel, Purvish; Rousseaux, Sophie A. L. (Synlett, 2020)
α-Aryl amines are prevalent in pharmaceutically active compounds and natural products. Herein, we describe a Ni-catalyzed protocol for their synthesis from readily available α-aryl ethers. While α-aryl ethers have been used as electrophiles in Ni-catalyzed C–C bond formations, their use in C–heteroatom bond formation is much less prevalent. Preliminary mechanistic insight suggests that oxidative addition is facilitated by an anionic ligand and that reductive elimination is a reversible process.
Keywords: nickel catalysis; α-aryl amines; α-aryl ethers